A Modified Balanced Scorecard Based Hybrid Pythagorean Fuzzy AHP-Topsis Methodology for ATM Site Selection Problem - Yildiz, Aslihan; Ayyildiz, Ertugrul; Gumus, Alev Taskin; Ozkan, Coskun (WORLD SCIENTIFIC PUBL CO PTE LTD, 2020)
Researchers work on facility location problems in different structures and solve them by developing different models over the years. In this study, we focus on the automated teller machine (ATM) site selection problem for a public bank in Istanbul. Twenty-five districts, which are located at the European side of Istanbul, are designated as ATM candidate districts. The balanced scorecard (BSC) model is modified to determine the criteria according to the literature review and experts' judgments for this problem. Internal, Customer, and Financial perspectives of the traditional BSC model are used as the main criteria and an external perspective is considered as the fourth criterion for modified balanced scorecard. The experts' criteria evaluations are gained and consolidated by the Modified Delphi Method. The criteria weights are determined by the Pythagorean Fuzzy-AHP method using the final pairwise comparison results obtained from the Modified Delphi Method. Subsequently, the Pythagorean Fuzzy TOPSIS method is applied to determine the best alternative site among alternatives to locate the ATM according to these criteria. Finally, the results are presented and discussed by sensitivity analysis.
Keywords: ATM; pythagorean fuzzy-AHP; pythagorean fuzzy TOPSIS; GROUP DECISION-MAKING; OCCUPATIONAL-HEALTH; LOCATION; SAFETY; DELPHI; MODEL; FIRMS; Computer Science; Operations Research & Management Science